Effects of inert dilution on the lean blowout characteristics of syngas flames. (8th June 2016) - Li, Suhui; Zhang, Xiaoyu; Zhong, Di; Weng, Fanglong; Li, Shaoshuai; Zhu, Min
Abstract: The paper presents an experimental study on the lean blowout (LBO) characteristics of inert-diluted syngas fuels. Real syngas fuels often contain inert diluents such as N2 and CO2 . The diluents have negative impact on the syngas flame stability, which needs to be understood for the design and operation of gas turbine and industrial burners. In this work, effects of diluents on the LBO of premixed syngas flames were systematically studied under atmospheric pressure using a swirling flow model combustor. LBO limits, i.e., the equivalence ratio at which the flame blows out, were measured for syngas mixtures with various dilution ratios. Results show that the LBO limits generally increase with dilution ratio. In particular, inert dilution dominates the LBO behavior of syngas which has low H2 content. Detailed analyses based on a well stirred reactor model reveal that the experimental data can be well explained by the thermal and chemical kinetics effects of diluents. A physics-based correlation, using Damköhler number and normalized flame temperature, is proposed for the prediction of LBO limits of inert-diluted syngas flames. Highlights: Lean blowout (LBO) limit of syngas flame increases with inert dilution ratio. The increase is due to the thermal and chemical kinetics effects of diluents. The thermal effects can be quantified by the flame temperature. The chemical effects can be quantified by the chemical time (Damköhler number). LBO limit can be predicted by the flame temperature-Damköhler number correlation.